2001
DOI: 10.1212/wnl.57.2.348
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of myelopathies in HIV seropositive South African patients

Abstract: The authors determined the cause of myelopathies in 33 HIV seropositive individuals in KwaZulu/Natal, South Africa. The main associations were with human T-cell lymphotrophic virus-I, tuberculosis, herpes zoster, and syphilis. A novel association with probable bilharziasis was noted. Only one case of vacuolar myelopathy was identified. Opportunistic infections will probably persist until routine antiretroviral therapy becomes widely available in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 8 publications
0
33
1
Order By: Relevance
“…The presentation should be differentiated from the vacuolar myelopathy seen with HIV infection alone. 1,5 A further unusual and unique feature was the normality of the CSF examination. Although in cases of tuberculous abscess, the CSF may be normal until rupture occurs into the subarachnoid space, a lymhocytosis, raised protein and possibly hypoglycorrachia would have been expected even in a treated and sterile CSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presentation should be differentiated from the vacuolar myelopathy seen with HIV infection alone. 1,5 A further unusual and unique feature was the normality of the CSF examination. Although in cases of tuberculous abscess, the CSF may be normal until rupture occurs into the subarachnoid space, a lymhocytosis, raised protein and possibly hypoglycorrachia would have been expected even in a treated and sterile CSF.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] It may arise as a primary manifestation of the infection, by downward extension of tuberculous meningitis, or by spread from a vertebral osteomyelitis. 3 It is not uncommon for it to develop during treatment for a primary infection elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…4 Bhigjee et al previously found a co-infection rate of HIV and HTLV-1 in 6% -8% of patients with HAM. In a study on the spectrum of myelopathies in HIV positive patients in South Africa, 5 they found that 33% of patients had seropositivity for both HIV and HTLV-1, suggesting a higher frequency of myelopathy in co-infected patients. In addition, the patients were younger than those without HIV infection, but otherwise similar, without profound immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…About half of all patients with HAM currently seen at the Steve Biko Academic Hospital are infected with HIV, compared with 33% in KwaZulu-Natal. 5 Co-infection of HTLV-1 and HIV in patients with HAM has been mentioned in several studies. 4,5,14,15 According to Berger et al, 16 patients co-infected with HIV/HTLV are at increased risk for developing HAM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation